ECO, Umberto; CARRIÈRE, Jean-Claude. Não contem com o fim do livro. Trad. André Telles. Rio de Janeiro: Record, 2010. 269p. - Diniz, Davidson Oliveira (Aletria: Revista de Estudos de Literatura, 2010)
.